TESTING HARDENED CONCRETE USING THE MATURITY CONCEPT - George Ilinoiu (Civil Engineering Dimension, 2003)
The paper provides an overview of different methods that can be used for concrete maturity determination, outlining Romanian Concrete Code Specification (NE 012-99) in relation to using an effective and rational method in evaluating in-situ concrete strength at different ages.